Common Social Work Education Standards in the Nordic Countries - opening an issue - Petersson, Sigrun Juliusdottir and Jan (2003)
The article analyses the option of common Nordic Standards for social work education in these countries. The option is viewed through the lens of trends in education in the different countries. In the article the notion of an Integrated Field Model is used to indicate the starting point for a common model of education. This model covers the field characteristics of Denmark and Norway and their current move towards a more research-based education. It also covers the research characteristics of education in Finland, Iceland and Sweden and their current move towards a new field connection based on research-oriented education. Some thoughts on international requirements on comparability and compatibility in this setting are addressed in the final section.